2019
DOI: 10.2166/wp.2019.229
|View full text |Cite
|
Sign up to set email alerts
|

Water management systems of two towns in the Eastern Himalaya: case studies of Singtam in Sikkim and Kalimpong in West Bengal states of India

Abstract: This study examines the water supply systems, their sociopolitical dynamics, and the future of water management in two Indian towns in the Eastern Himalaya, Kalimpong in West Bengal and Singtam in Sikkim. The research was centred around issues of demand and supply, water scarcity and stress, equity, water governance, and the sustainable conservation and management of water resources in a climate change context. Methodologically based on surveys, focus group discussions, and key informants' interviews, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In 2018, MSW was collected through community bins and transported by municipal trucks on a predetermined schedule signified to households with the ringing of a bell (Sharma et al 2020 ; Interview B and C). These trucks took the waste to a dumping site in Martam, approximately 20 km away from Gangtok center (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, MSW was collected through community bins and transported by municipal trucks on a predetermined schedule signified to households with the ringing of a bell (Sharma et al 2020 ; Interview B and C). These trucks took the waste to a dumping site in Martam, approximately 20 km away from Gangtok center (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Known for its scenic beauty, snow-clad Himalayas, and tea gardens, Darjeeling is frequented by tourists from all over the country as well as from around the world. Especially during the summers, the place is a preferred destination due to its pleasant weather [5]. Kalimpong is an important town in the Darjeeling Himalaya with a population size of 49,403 (Census 2011) and spread over 23 wards in 3.5 sq km.…”
Section: Delineation Of the Study Areamentioning
confidence: 99%
“…Earlier, Deolo reservoir, fed by these streams, always had about 8 lakh gallons of water. But for the past 15-20 days it has come down to 3.5 lakh gallons to 5 lakh gallons [5].…”
Section: Delineation Of the Study Areamentioning
confidence: 99%
“…Saleth (2000) analyzed the water institutional developments in 11 countries including India and demonstrated that the structural shifts exist in the water sector due to the endogenous factors (water shortages, output degradation, and financial unattainable) as well as exogenous factors (macroeconomic instability, democratic transformation, natural disasters, and technical advancement). Many researchers have attempted to propose a national water demand management policy in India to manage demand and improve water use efficiency (Asthana, 2011; Gopakumar, 2010; Meijerink & Huitema, 2010; Singh et al., 2013), interbasin water transfers (Gupta & Zaag, 2008; Sharma et al., 2019), and groundwater policy (Katyaini & Barua, 2016; Shah, 2009). Shen and Reddy (2016) explored the complex problems driving water pricing reform and opined that China and India are on the same water pricing path and course, but China has advanced a little further.…”
Section: Introductionmentioning
confidence: 99%